2007
DOI: 10.1074/jbc.m608166200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Metalloprotease Botulinum Serotype A from a Pseudo-peptide Binding Mode to a Small Molecule That Is Active in Primary Neurons

Abstract: An efficient research strategy integrating empirically guided, structure-based modeling and chemoinformatics was used to discover potent small molecule inhibitors of the botulinum neurotoxin serotype A light chain. First, a modeled binding mode for inhibitor 2-mercapto-3-phenylpropionyl-RATKML (K i ‫؍‬ 330 nM) was generated, and required the use of a molecular dynamic conformer of the enzyme displaying the reorientation of surface loops bordering the substrate binding cleft. These flexible loops are conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(159 citation statements)
references
References 44 publications
12
145
1
1
Order By: Relevance
“…Compounds 1-4 were docked in the BoNT/A LC substrate binding cleft to determine if they would also engage in intermolecular contacts that were comparable to those predicted for other structurally diverse SMNPIs. [31][32][33] Similar to our previously docked models of ACQ inhibitors, 31,32 the 7-chloro substituents of 1-3 ( Figure 3A-C) and one of the ACQs of 4 ( Figure 4A and B) engage in favorable hydrophobic contacts with residues Phe 162, Phe 163, and Thr 219 of hydrophobic binding subsite 1 [31][32][33] (also described as the S1′ binding site 34 ). At the same time, the quinoline nitrogens of the inhibitors are positioned so that this heteroatom may interfere with the enzyme's catalytic engine.…”
Section: Molecular Docking Of Smnpis 1-4 Demonstrates a Consistency Wsupporting
confidence: 74%
See 1 more Smart Citation
“…Compounds 1-4 were docked in the BoNT/A LC substrate binding cleft to determine if they would also engage in intermolecular contacts that were comparable to those predicted for other structurally diverse SMNPIs. [31][32][33] Similar to our previously docked models of ACQ inhibitors, 31,32 the 7-chloro substituents of 1-3 ( Figure 3A-C) and one of the ACQs of 4 ( Figure 4A and B) engage in favorable hydrophobic contacts with residues Phe 162, Phe 163, and Thr 219 of hydrophobic binding subsite 1 [31][32][33] (also described as the S1′ binding site 34 ). At the same time, the quinoline nitrogens of the inhibitors are positioned so that this heteroatom may interfere with the enzyme's catalytic engine.…”
Section: Molecular Docking Of Smnpis 1-4 Demonstrates a Consistency Wsupporting
confidence: 74%
“…31 In a subsequent molecular dynamics study, we demonstrated that conformationally flexible loops surrounding the BoNT/A LC substrate binding cleft may reorient to decrease the solvent accessibility of the cleft (as compared to respective energy refined structures), while simultaneously providing more hydropathically feasible binding contacts for SMNPIs. 32 The molecular dynamics studies were pivotal for identifying a binding mode 33 for the potent pseudo-peptide inhibitor 2-mercapto-3-phenylpropionyl-RATKML (mpp-RAT-KML, K i ) 330 nM 34 ). In the same study, we also proposed new pharmacophore components and constraints based on the docked model of mpp-RATKML, and, using this information, we identified more potent SMNPIs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one compound (NA-A1B2C10) showed the least protection of SNAP-25 cleavage in cellular assays at 25 M, whereas the other (2,4-dichlorocinnamic hydroxamic acid) was found to be cytotoxic in neuroblastoma cells at concentrations three orders of magnitude less than those tested in animals (i.e., 5 M). Numerous cellbased assays have been developed for assessing BoNT toxicity, including cultured murine neuroblastoma cells (Neuro-2a) (38), primary rodent fetal spinal cord cells (35,39,40), cultured chicken spinal motor neurons (16), and rat adrenal pheochromocytoma cells (PC12) (41). One of the major advantages of a secondary screen such as cell-based assays is a considerable reduction in the number of animals used, time expended, and cost incurred, especially when used for assessing large numbers of target molecules.…”
Section: In Vivo Examination Of Lead Compoundsmentioning
confidence: 99%
“…A complementary approach used by our laboratory and others has focused on metal chelators, which presumably bind the active site zinc cation, thereby rendering the BoNT LC inactive (12)(13)(14). Analogous to these approaches, others have used an in silico screen of a large compound library in an effort to identify BoNT/A-selective inhibitors and establish a pharmacophore for BoNT/A LC inhibition; again, the most effective compounds identified by using this approach operated by zinc chelation (15,16). However, it is important to note that this pharmacophore has been established from in vitro methods, with scant in vivo data for any reported compound.…”
mentioning
confidence: 99%
“…BoNT antagonist development has been largely limited to studies of small sets of compounds or peptides chosen through rational design, computer-assisted, or other methods [54][55][56][57][58][59]. Although these studies have provided a considerable amount of information about BoNT catalytic mechanism and substrate requirements, few of the small molecule inhibitors that have emerged from these studies have sufficient potency to be effective BoNT therapeutics.…”
Section: Discussionmentioning
confidence: 99%